Impact of Education on COPD Severity and All-Cause Mortality in Lifetime Never-Smokers and Longtime Ex-Smokers: Results of the COSYCONET Cohort - Lutter JI; Jörres RA; Welte T; Watz H; Waschki B; Alter P; Trudzinski FC; Ohlander J; Behr J; Bals R; Studnicka M; Holle R; et al. (International Journal of COPD, 2020)
Johanna I Lutter,1 Rudolf A Jörres,2 Tobias Welte,3 Henrik Watz,4 Benjamin Waschki,5 Peter Alter,6 Franziska C Trudzinski,7 Johan Ohlander,1,8 Jürgen Behr,9 Robert Bals,10 Michael Studnicka,11 Rolf Holle,12 Claus F Vogelmeier,6 Kathrin Kahnert9 1Institute of Health Economics and Health Care Management, Helmholtz Zentrum München GmbH - German Research Center for Environmental Health, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research, Munich, Germany; 2Institute and Outpatient Clinic for Occupational, Social and Environmental Medicine, Comprehensive Pneumology Center Munich (CPC-M), Ludwig-Maximilians-Universität München, Munich 80336, Germany; 3Department of Pneumology, Hannover Medical School, Hannover 30625, Germany; 4Pulmonary Research Institute at Lungen Clinic Grosshansdorf, Airway Research Center North (ARCN), Member of the German Center for Lung Research (DZL), Grosshansdorf 22927, Germany; 5Department of General and Interventional Cardiology, University Heart Center Hamburg, Hamburg, Germany; 6Department of Medicine, Pulmonary and Critical Care Medicine, University Medical Center Giessen and Marburg, Philipps-University Marburg (UMR), Germany, Member of the German Center for Lung Research (DZL), Marburg 35043, Germany; 7Department of Diagnostic & Interventional Radiology, University Hospital of Heidelberg, Heidelberg, Germany; 8Institute for Risk Assessment Sciences, Utrecht University, Utrecht 3584 CM, Netherlands; 9Department of Internal Medicine V, University of Munich (LMU), Comprehensive Pneumology Center, Member of the German Center for Lung Research (DZL), Munich, 80336, Germany; 10Department of Internal Medicine V – Pulmonology, Allergology, Respiratory Intensive Care Medicine, Saarland University Hospital, Homburg 66424, Germany; 11Department of Pneumology, Paracelsus Medical University Salzburg, Universitätsklinikum Salzburg, Salzburg 5020, Austria; 12Institute for Medical Informatics, Biometry and Epidemiology, University Hospital Ludwig-Maximilians-University Munich (LMU), Munich 81377, GermanyCorrespondence: Kathrin KahnertDepartment of Internal Medicine V, University of Munich (LMU), Comprehensive Pneumology Center, Member of the German Center for Lung Research (DZL), Ziemssenstr. 1, Munich 80336, GermanyEmail Kathrin.Kahnert@med.uni-muenchen.deBackground: Beyond smoking, several risk factors for the development of chronic obstructive pulmonary disease (COPD) have been described, among which socioeconomic status including education is of particular interest. We studied the contribution of education to lung function and symptoms relative to smoking in a group of never-smokers with COPD compared to a group of long-time ex-smokers with COPD.Methods: We used baseline data of the COSYCONET cohort, including patients of GOLD grades 1– 4 who were either never-smokers (n=150, age 68.5y, 53.3% female) or ex-smokers (≥ 10 packyears) for at least 10 years (n=616, 68.3y, 29.9% female). Socioeconomic status was analyzed using education level and mortality was assessed over a follow-up period of 4.5 years. Analyses were performed using ANOVA and regression models.Results: Spirometric lung function did not differ between groups, whereas CO diffusing capacity and indicators of lung hyperinflation/air-trapping showed better values in the never-smoker group. In both groups, spirometric lung function depended on the education level, with better values for higher education. Quality of life and 6-MWD were significantly different in never-smokers as well as patients with higher education. Asthma, alpha-1-antitrypsin deficiency, and bronchiectasis were more often reported in never-smokers, and asthma was more often reported in patients with higher education. Higher education was also associated with reduced mortality (hazard ratio 0.46; 95% CI 0.22– 0.98).Conclusion: Overall, in the COSYCONET COPD cohort, differences in functional status between never-smokers and long-time ex-smokers were not large. Compared to that, the dependence on education level was more prominent, with higher education associated with better outcomes, including mortality. These data indicate that non-smoking COPD patients’ socioeconomic factors are relevant and should be taken into account by clinicians.Keywords: COPD, never-smoker, education, socioeconomic status